Comparison of maternal outcome in patients treated with methyldopa and labetalol in the management of hypertensive disorders of pregnancy - K. M., Harish; N., Shwetha; Debnath, Dipankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To compare the maternal outcome in patients treated with methyldopa and labetalol in the management of moderate to severe hypertensive disorders of pregnancy (HDP). Methods: The present study is Prospective parallel group comparative study on 200 out-patients and inpatients selected between January 2013 to December 2013 from OPD and antenatal ward of Obstetrics and Gynaecology department, of tertiary care teaching hospital, Regional Institute of Medical Sciences, Imphal. 100 patients each were distributed to methyldopa group and labetalol group respectively. Results: There was statistically significant reduction in the mean systolic BP + Standard deviation / Diastolic BP + Standard deviation and Mean arterial pressure (MAP) in Labetalol group (from 156.84 + 5.75/100.20 + 6.02 mmHg and 119.08 + 4.07 to 133.76 + 3.50/85.14 + 3.98 mmHg and 101.35 + 2.94) compared to Methyldopa group (from 156.00 + 6.581/100.96 + 6.896mmHg and 119.30 + 4.86 to 137.20 + 2.36/89.02 + 2.38mmHg and 105.08 + 1.78). Risk of adverse effects was less in Labetalol group (12%) but complication during pregnancy was more in Methyldopa group (51%). Number of spontaneous onset of labour and vaginal mode of delivery was more in Labetalol group. Conclusions: The present study shows that primiparity, residing in rural area, with low income group and overweight are at high risk of developing Hypertensive Disorders of Pregnancy. Labetalol is the better drug in controlling blood pressure with less adverse effects and maternal complication.